A Case Report Overwhelming response to TNF-alfa inhibitor Infliximab “innovator” Vs. Adalimumab “Bio-similar” in a previously therapy naive adult - Yadav, Kanishk (Indian Journal of Case Reports, 2022)
Therapeutic options for patients with Spondyloarthritis (SpA) are limited. The present-day pharmacotherapy for Spondyloarthritis comprises immunomodulator/suppressive drugs. In this case report, we describe a 29-year old Postgraduate resident in Medicine who was diagnosed with spondyloarthritis and was managed by a combination of various disease-modifying drugs like methotrexate and sulfasalazine and immunomodulators such as systemic corticosteroids as well as Tumor Necrosis Factor-alfa inhibitors. After a series of therapeutic trials with them, the chimeric TNF blocker Infliximab led to significant clinical improvement in symptoms and reduction in disease activity.